2022
DOI: 10.3389/fbioe.2022.917655
|View full text |Cite
|
Sign up to set email alerts
|

Microporous structures on mineralized collagen mediate osteogenesis by modulating the osteo-immune response of macrophages

Abstract: It is a new hot pot in tissue engineering and regenerative medicine to study the effects of physicochemical properties of implanted biomaterials on regulating macrophage polarization to promote bone regeneration. In this study, we designed and fabricated mineralized collagen (MC) with different microporous structures via in vitro biomimetic mineralization method. The microporous structures, mechanical properties, shore hardness and water contact angle measurements were tested. Live/dead cell staining, CCK-8 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Li et al . observed no difference in viability at days 1 and 2 with Col-I modified samples, but noted changes in cytoskeleton and focal adhesion at day 3, suggesting delayed effects of surface properties on these aspects of cell behavior that could ultimately influence viability and macrophage polarization 87 . Finally, Neacsua et al found that the addition of the M1 macrophage phenotype stimulator LPS resulted in decreased viability of macrophages on TiO 2 nanotubes, while Schaub et al .…”
Section: Resultsmentioning
confidence: 87%
“…Li et al . observed no difference in viability at days 1 and 2 with Col-I modified samples, but noted changes in cytoskeleton and focal adhesion at day 3, suggesting delayed effects of surface properties on these aspects of cell behavior that could ultimately influence viability and macrophage polarization 87 . Finally, Neacsua et al found that the addition of the M1 macrophage phenotype stimulator LPS resulted in decreased viability of macrophages on TiO 2 nanotubes, while Schaub et al .…”
Section: Resultsmentioning
confidence: 87%
“…Li et al found that MC can promote bone defect repair by regulating the local bone immune environment. MC of medium pore size can significantly enhance the osteogenic differentiation of MC3T3-E1 in the macrophage environment and promote the expression of OCN and ALP [ 60 ].…”
Section: Resultsmentioning
confidence: 99%